2019
DOI: 10.1002/ejhf.1666
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes increases the long‐term risk of heart failure and mortality in patients with atrial fibrillation

Abstract: Aims Impact of type 2 diabetes mellitus (T2DM) on non‐thromboembolic outcomes in atrial fibrillation (AF) is insufficiently explored. This prospective cohort study of AF patients aimed (i) to analyse the association between T2DM and heart failure (HF) events (including new‐onset HF), and all‐cause and cardiovascular mortality, (ii) to assess the impact of baseline T2DM treatment on outcomes, and (iii) to explore characteristics of new‐onset HF phenotypes in relation to T2DM status. Methods and results Of 1803 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 63 publications
(149 reference statements)
0
23
3
Order By: Relevance
“…Competing-risk regression analysis showed that patients with DM did not exhibit a significant increase in hospitalizations for AF or HF related complications, in comparison with those without DM. This is in contrast to similar studies, in which DM significantly increased the long-term risk of hospitalization in patients with AF [24,25]. The analysis on major bleeding events did not correlate with the increased risk for bleeding in DM implied by the HAS-BLED score, possibly due to the sparse events.…”
Section: Discussioncontrasting
confidence: 99%
“…Competing-risk regression analysis showed that patients with DM did not exhibit a significant increase in hospitalizations for AF or HF related complications, in comparison with those without DM. This is in contrast to similar studies, in which DM significantly increased the long-term risk of hospitalization in patients with AF [24,25]. The analysis on major bleeding events did not correlate with the increased risk for bleeding in DM implied by the HAS-BLED score, possibly due to the sparse events.…”
Section: Discussioncontrasting
confidence: 99%
“…Competing-risk regression analysis showed that patients with DM did not exhibit a signi cant increase in hospitalizations for AF or HF related complications, in comparison with those without DM. This is in contrast to similar studies, in which DM signi cantly increased the long-term risk of hospitalization in patients with AF 24,25 . The analysis on major bleeding events did not correlate with the increased risk for bleeding in DM implied by the HAS-BLED score, possibly due to the sparse events.…”
Section: Discussioncontrasting
confidence: 99%
“…Type 2 diabetes mellitus confers a greater risk of new onset HF, HF rehospitalization, and CV and all‐cause mortality, particularly when patients require insulin treatment and/or have concomitant conditions 46–51 …”
Section: Co‐morbiditiesmentioning
confidence: 99%